Dynamic processes of students learning on initial teacher training - Gouveia, Fernanda (2020)
The debate about the importance of learning through participation in the initial teacher training is relevant in dynamic processes of students learning, that happens according to the action in the context, the culture and social interaction. We intend to emphasize how important is the experience in personal and professional training of students learning in Action-Research (A-R). Through a qualitative study it was possible to interpret the learning processes to develop an important trajectory regarding the initial teacher training. Learning in real contexts was a challenge in the initial formation of students and made it possible to reflect critically their practices.